Potential, Pitfalls, and Future Directions for Remote Monitoring of Chronic Respiratory Diseases: Multicenter Mixed Methods Study in Routine Cystic Fibrosis Care - Martinus C Oppelaar; Yvette Emond; Michiel A G E Bannier; Monique H E Reijers; Hester van der Vaart; Renske van der Meer; Josje Altenburg; Lennart Conemans; Bart L Rottier; Marianne Nuijsink; Lara S van den Wijngaart; Peter J F M Merkus; et al. (JMIR Publications, 2024)
BackgroundThe current literature inadequately addresses the extent to which remote monitoring should be integrated into care models for chronic respiratory diseases (CRDs). ObjectiveThis study examined a remote monitoring program (RMP) in cystic fibrosis (CF) by exploring experiences, future perspectives, and use behavior over 3 years, with the aim of developing future directions for remote monitoring in CRDs. MethodsThis was a mixed methods, multicenter, observational study in 5 Dutch CF centers following a sequential explanatory design. Self-designed questionnaires using the technology acceptance model were sent out to people with CF who had a minimum of 12 months of experience with the RMP and local health care professionals (HCPs). Questionnaire outcomes were used to inform semistructured interviews with HCPs and people with CF. Qualitative findings were reported following the COREQ (Consolidated Criteria for Reporting Qualitative Research) checklist. Anonymous data on use frequency of all people with CF were analyzed. ResultsBetween the second quarter of 2020 and the end of 2022, a total of 608 people with CF were enrolled in the program, and a total of 9418 lung function tests and 2631 symptom surveys were conducted. In total, 65% (24/37) of HCPs and 89% (72/81) of people with CF responded to the questionnaire, and 7 HCPs and 12 people with CF participated in semistructured interviews. Both people with CF and HCPs were positive about remote monitoring in CF care and found the RMP a good addition to daily care (people with CF: 44/72, 61%; HCPs: 21/24, 88%). Benefits ranged from supporting individual patients to reducing health care consumption. The most valued monitoring tool was home spirometry by both people with CF (66/72, 92%) and HCPs (22/24, 92%). Downsides included the potential to lose sight of patients and negative psychosocial effects, as 17% (12/72) of people with CF experienced some form of stress due to the RMP. A large majority of people with CF (59/72, 82%) and HCPs (22/24, 92%) wanted to keep using the RMP in future, with 79% (19/24) of HCPs and 75% (54/72) of people with CF looking forward to more replacement of in-person care with digital care during periods of well-being. Future perspectives for the RMP were centered on creating hybrid care models, personalizing remote care, and balancing individual benefits with monitoring burden. ConclusionsRemote monitoring has considerable potential in supporting people with CF and HCPs within the CF care model. We identified 4 practice-based future directions for remote monitoring in CF and CRD care. The strategies, ranging from patient driven to prediction driven, can help clinicians, researchers, and policy makers navigate the rapidly changing digital health field, integrate remote monitoring into local care models, and align remote care with patient and clinician needs.